2019
DOI: 10.3390/f10070558
|View full text |Cite
|
Sign up to set email alerts
|

Sand Dune Height Increases Water Use Efficiency at the Expense of Growth and Leaf Area in Mongolian Pine Growing in Hulunbeier Steppe, Inner Mongolia, China

Abstract: The Mongolian pine (Pinus sylvestris var. mongolica) is one of the most common tree species in semiarid and arid areas of China, especially in the sand dunes of the Hulunbeier steppe. This study addresses the morphological and physiological characteristics of the Mongolian pine according to sand dune height. Five sites were chosen with various sand dune heights (P1–P5). Nine years after planting, tree growth, leaf area, leaf mass per leaf unit area (LMA), diameter at breast height (DBH), tree height, diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…In this study, mean temperature of the quarter showed little significance in morphological traits, perhaps due to all sampling sites belonging to the subtropical monsoon climate and no strict temperature limit for persimmon survival. Consistent with previous studies of many fruit trees, which revealed that light [59][60][61] and water supply [62][63][64][65][66] played an important cue in both leaf and fruit development, and precipitation and solar radiation were the main climate factors affecting the morphological traits of persimmon in Zhejiang Province. There were also longitudinal differences in morphological trait diversity.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, mean temperature of the quarter showed little significance in morphological traits, perhaps due to all sampling sites belonging to the subtropical monsoon climate and no strict temperature limit for persimmon survival. Consistent with previous studies of many fruit trees, which revealed that light [59][60][61] and water supply [62][63][64][65][66] played an important cue in both leaf and fruit development, and precipitation and solar radiation were the main climate factors affecting the morphological traits of persimmon in Zhejiang Province. There were also longitudinal differences in morphological trait diversity.…”
Section: Discussionsupporting
confidence: 90%
“…A survey of Liaoning Province revealed that 62.75% of the trees in the Mongolian pine forests (in total 38,300 ha, of which the majority were high-density stands) declined in condition [25]. Previous studies on this species focused on the relationship between growth and climatic variables [26], intrinsic water use efficiency [27], sap flow and canopy water use [28], hydraulic limits underlying the low growth rate [21], and stand decline resulting from land use [29]. However, few studies investigated the response and adaptation of Mongolian pine in stands of different densities to drought, especially severe drought events.…”
Section: Introductionmentioning
confidence: 99%